Potential and Challenges of Hydrogen Development as New Renewable Energy in Indonesia - Efrando Manullang; Nazaruddin Sinaga (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2022)
The use fossil energy consumption in Indonesia is increasing along with population growth and industrial development. Fossil energy oil and coal can produce greenhouse gas emissions and environment pollution. The largest producer of CO2 emissions comes from exhaust gases in the production process and motor vehicles. Indonesia's energy mix target in 2025 is around 23% from New and Renewable Energy (NRE). Given the importance of using NRE, Indonesia is starting to look for alternative energy that is environmentally and sustainable, like hydrogen energy. Green hydrogen technology has the potential to be developed in Indonesia. Hydrogen production processes commonly carried out are through the electrolysis of water, methanol, and biomass. The use of hydrogen can be applied to motor vehicles and power plants. Hydrogen can reduce greenhouse gas emissions. However, Indonesia has problems in developing green hydrogen technology, one of which is the high production cost, so it requires other parties to develop it.